STRATEGI PENGEMBANGAN USAHA TAHU PADA INDUSTRI TAHU MITRA CEMANGI KOTA PALU - Dirwan, Dirwan; Hamzens, Wildani Pingkan S; Alamsyar, Al (Fakultas Pertanian, Universitas Tadulako, 2023)
Tofu, a processed soy product, has undergone continuous innovation, evolving from a simple fried snack sold on roadsides to becoming a prominent item on the menus of large restaurants. In Indonesia, people show less interest in consuming raw soybeans and prefer processed options, with tofu being one of their preferred choices. This study was carried out at Mitra Cemangi Tofu industry located in Bayoge Village, Tatanga Sub District of Palu City. The choice of this location was intentional as Mitra Cemangi is a prominent tofu business in Palu City. The research was conducted between March and April 2020, with five purposively selected respondents: one leader and two employees and two consumers. The analysis utilized the SWOT method, which revealed a rating value of 1.71 for the internal strategic factors and 1.21 for the external factors in the development of the Nitra Cemangi Tofu Industry business. It was determined that the appropriate development strategy for the Mitra Cemangi Tofu Industry is the S-O strategy. This strategy focuses on leveraging strengths to capitalize on existing opportunities and can prove beneficial for the growth of the Tofu Mitra Cemangi Industry.